Diaphragm for semi-solid or solid battery as well as preparation method and application of diaphragm
By designing a three-layer membrane structure and utilizing differentiated high-density polyethylene and white oil, the porosity and pore size of the membrane were improved, solving the problem of insufficient electrolyte capacity in existing membranes in semi-solid or solid-state batteries and enhancing battery performance.
Patent Information
- Application Number
- CN202411975419.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Existing separators, when used in semi-solid or solid-state batteries, have low porosity and small pore size, which makes it impossible to effectively accommodate a large amount of electrolyte.
The membrane is designed with a three-layer structure. The middle layer uses low flash point white oil and high-density polyethylene with a high dispersion coefficient, while the surface layer uses high initial boiling point white oil and high molecular weight high-density polyethylene. The porosity and pore size are improved by evaporation to form pores.
It achieves higher porosity and pore size in solid-state or semi-solid-state batteries, which can effectively accommodate more electrolyte and improve battery capacity and conductivity.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery separators, and in particular to a separator for semi-solid or solid batteries and a preparation method and application thereof. Background Art
[0002] At present, the batteries used on a large scale in the new energy industry are liquid lithium-ion batteries. Although liquid lithium batteries have high conductivity, they also have problems such as low energy density, electrolyte leakage, flammability and explosion, and lithium dendrites are prone to piercing the diaphragm and causing battery short circuits during the charging and discharging process. Compared with liquid batteries, semi-solid or solid-state batteries use semi-solid or solid electrolytes, use only less or no electrolyte, and have the advantages of high safety, wide electrochemical window and high energy density. Therefore, the development of semi-solid or solid electrolytes is an important direction for promoting the development of new energy.
[0003] As an important component of the battery, in addition to the positive electrode, negative electrode, and electrolyte, the battery separator plays a vital role in the battery. The battery separator material is an insulating film containing a large number of microporous structures, and its main components are insulating olefin polymer materials. The separator has two main functions: one is to isolate the positive and negative electrodes in the battery to prevent the two electrodes from directly contacting and short-circuiting. At the same time, it needs to be as thin as possible while ensuring safety to reduce the distance between the two electrodes and reduce the internal resistance of the battery; the other is to be able to store and maintain sufficient electrolyte. The microporous structure allows the Li in the electrolyte to + Free passage, achieving Li + Rapid transmission between the positive and negative electrodes. Therefore, the temperature resistance, wettability to the electrolyte, adhesion to the electrodes and other properties of the battery separator can directly affect the key properties of the lithium battery, such as capacity, cycle performance and charge and discharge current density.
[0004] With the development of semi-solid or solid-state batteries, new requirements are put forward for separators, such as high porosity and large pore size, which are conducive to filling more electrolytes. However, when traditional separators are used in semi-solid or solid-state batteries, they cannot effectively accommodate more electrolytes due to their low porosity and small pore size. Summary of the invention
[0005] In order to solve the above technical problem, that is, the existing diaphragm has low porosity and small pore size when used in semi-solid or solid batteries, resulting in the inability to effectively accommodate more electrolytes, the present invention provides a diaphragm for semi-solid or solid batteries and a preparation method and application thereof. The diaphragm of the present invention has a larger pore size and higher porosity, and can effectively accommodate more electrolytes when used in solid or semi-solid batteries.
[0006] The specific technical scheme of the present invention is: In the first aspect, the present invention provides a semi-solid or solid battery separator, comprising an upper surface layer, an intermediate layer and a lower surface layer arranged in sequence from top to bottom; the raw materials of the intermediate layer include: a weight average molecular weight of 2×10 5 ~3×10 5 Da and a polydispersity coefficient of 12 to 20, and a white oil with a flash point not higher than 80°C; the raw materials of the upper surface layer and the lower surface layer include: a weight average molecular weight of 6×10 5 ~1×10 6 Da high-density polyethylene, white oil with an initial distillation point higher than the diaphragm molding temperature.
[0007] The present invention designs the diaphragm into a three-layer structure, and uses differentiated high-density polyethylene and white oil in the surface layer (upper surface layer and lower surface layer) and the middle layer. With the cooperation of these raw materials, the diaphragm can have a larger pore size and higher porosity, so that the diaphragm can effectively accommodate more electrolytes when used in solid-state or semi-solid-state batteries. Specifically, the cooperation between the raw materials in the three layers is as follows: (1) White oil in the middle layer: The white oil used in the middle layer has a low flash point (not higher than 80°C) and is easy to volatilize. Therefore, in the process of using white oil to make holes, there is no need to remove the white oil by extraction, and holes can be formed by volatilization. Since the pore-forming method is a dynamic volatilization method rather than a static extraction method, a larger porosity and pore size can be obtained during the volatilization process.
[0008] (2) High-density polyethylene in the middle layer: The high-density polyethylene used in the middle layer has a large polydispersity coefficient (12~20), that is, a wide molecular weight distribution range and a low weight average molecular weight (M w =2×10 5 ~3×10 5 Da), which enables the middle layer to use lower extrusion and processing temperatures, reduces the volatilization loss of white oil in the middle layer during the preparation and molding of the diaphragm, and allows more white oil to volatilize during the drying process after the diaphragm is formed, thereby playing a better pore-forming role. At the same time, the large polydispersity coefficient and low weight-average molecular weight of high-density polyethylene in the middle layer can also make the middle layer easy to expand in thickness as the white oil evaporates, further increasing the porosity and pore size of the diaphragm.
[0009] (3) White oil in the upper and lower surface layers: The initial distillation point of the white oil used in the surface layer is higher than the molding temperature of the diaphragm (the molding of the three-layer diaphragm usually includes the process of three-layer co-extrusion, casting and stretching). It is not easy to volatilize during the preparation and molding of the diaphragm, and can slow down the volatilization of the white oil in the middle layer, thereby reducing the premature volatilization loss of the white oil in the middle layer; and, during the drying process after the diaphragm is formed, the white oil in the surface layer is driven to leave the diaphragm together with the volatilization of the white oil in the middle layer. Due to the lower volatilization rate of the white oil on the surface layer, the volatilization process of the white oil in the middle layer can be made more controllable. In this way, the diaphragm can form a larger pore size as a whole and have a higher porosity.
[0010] (4) High-density polyethylene in the upper and lower surface layers: The high-density polyethylene used in the surface layer has a high weight average molecular weight (M w =6×10 5 ~1×10 6 Da), during the process of the white oil in the middle layer volatilizing and forming pores, the surface layer can support and restrict the middle layer, so that the thickness of the middle layer is more consistent after expansion.
[0011] Preferably, the raw materials of the intermediate layer include, by weight: 5 ~3×10 5 20 to 45 parts of high-density polyethylene with a Da and a polydispersity index of 12 to 20, 50 to 70 parts of white oil with a flash point not higher than 80°C, and 1 to 10 parts of an ion-conducting polymer.
[0012] Furthermore, the raw materials of the intermediate layer include, by weight: 5 ~3×10 5 20 to 45 parts of high-density polyethylene with a Da and a polydispersity index of 12 to 20, 50 to 70 parts of white oil with a flash point not higher than 80°C, and 5 to 10 parts of ion-conducting polymer.
[0013] In the middle layer, the ion-conducting polymer acts as a carrier for ion movement and has a high dielectric constant, which can reduce the dielectric impedance inside the battery and increase the transmission efficiency of lithium ions. Adding the ion-conducting polymer matrix to the separator can form a network that penetrates the inside of the separator and improve the ionic conductivity of the separator.
[0014] Preferably, the raw materials of the upper surface layer and the lower surface layer include, by weight: 5 ~1×10 6 30-50 parts of high-density polyethylene of Da, 50-70 parts of white oil with an initial boiling point higher than the diaphragm molding temperature.
[0015] Preferably, the high-density polyethylene in the middle layer has a melt index of 7-10 g / 10 min at 190°C and a melting point of no higher than 135°C; the viscosity of the white oil in the middle layer at 40°C is 1-5 mm 2 / s.
[0016] Preferably, the flash point of the white oil in the middle layer is 50-80°C.
[0017] Preferably, the polydispersity coefficient of the high-density polyethylene in the upper surface layer and the lower surface layer is less than 3, the melt index at 190°C is 0.1-2g / 10min, and the melting point is not less than 130°C; the initial boiling point of the white oil in the upper surface layer and the lower surface layer is not less than 220°C, and the viscosity at 40°C is 40-80mm 2 / s.
[0018] Furthermore, the initial distillation point of the white oil in the upper surface layer and the lower surface layer is 220-280°C.
[0019] Preferably, the ion-conducting polymer includes one or more of polyethylene oxide, polyacrylonitrile, polyvinyl alcohol and polymethyl methacrylate.
[0020] Preferably, the thickness of the diaphragm is 12-40 μm, and the thickness of the intermediate layer accounts for 40%-80% of the total thickness of the diaphragm.
[0021] In a second aspect, the present invention provides a method for preparing the diaphragm, comprising the steps of: mixing the raw materials of the upper surface layer, the middle layer and the lower surface layer respectively, performing three-layer co-extrusion, stretching after casting, and then drying to volatilize the white oil.
[0022] Preferably, during the three-layer co-extrusion process, the extrusion temperature is 160-200°C, the die temperature is 180-220°C; the temperature of the cast sheet is 50-80°C; the drying temperature is 110-140°C, and the time is 1-5 min; the stretching process includes: longitudinal stretching at 80-120°C and transverse stretching at 100-130°C.
[0023] In a third aspect, the present invention provides an application of the separator in a battery, wherein the battery is a solid-state battery or a semi-solid-state battery.
[0024] Compared with the prior art, the present invention has the following advantages: The present invention designs the diaphragm into a three-layer structure, and uses differentiated high-density polyethylene and white oil in the surface layer and the middle layer. Low flash point white oil and high-density polyethylene with a large polydispersity coefficient and a small molecular weight are used in the middle layer, and high initial distillation point white oil and high molecular weight high-density polyethylene are used in the surface layer. This can make the diaphragm have a larger pore size and a higher porosity, so that it can effectively accommodate more electrolytes when used in solid-state or semi-solid-state batteries. DETAILED DESCRIPTION
[0025] The present invention will be further described below in conjunction with the embodiments.
[0026] A semi-solid or solid battery separator, comprising an upper surface layer, an intermediate layer and a lower surface layer arranged in sequence from top to bottom; the raw materials of the intermediate layer include: a weight average molecular weight of 2×10 5 ~3×10 5 Da and a polydispersity coefficient of 12 to 20, and a white oil with a flash point not higher than 80°C; the raw materials of the upper surface layer and the lower surface layer include: a weight average molecular weight of 6×10 5 ~1×10 6 Da high-density polyethylene, white oil with an initial distillation point higher than the diaphragm molding temperature.
[0027] In some specific embodiments, the raw materials of the intermediate layer include, by weight: a weight average molecular weight of 2×10 5 ~3×10 5 Da and a polydispersity index of 12 to 20 high-density polyethylene 20 to 45 parts, a flash point of not higher than 80 ° C white oil 50 to 70 parts, ion-conducting polymer 1 to 10 parts. Optionally or preferably, the ion-conducting polymer includes one or more of polyethylene oxide, polyacrylonitrile, polyvinyl alcohol and polymethyl methacrylate; the weight portion of the ion-conducting polymer is 5 to 10 parts.
[0028] In some specific embodiments, the raw materials of the upper surface layer and the lower surface layer, by weight, both include: 5 ~1×10 6 30-50 parts of high-density polyethylene of Da, 50-70 parts of white oil with an initial boiling point higher than the diaphragm molding temperature.
[0029] In some specific embodiments, the high-density polyethylene in the middle layer has a melt index of 7 to 10 g / 10 min at 190°C and a melting point of no higher than 135°C; the viscosity of the white oil in the middle layer at 40°C is 1 to 5 mm 2 / s.
[0030] In some specific embodiments, the flash point of the white oil in the middle layer is 50-80°C.
[0031] In some specific embodiments, the polydispersity coefficient of the high-density polyethylene in the upper surface layer and the lower surface layer is less than 3, the melt index at 190°C is 0.1-2g / 10min, and the melting point is not less than 130°C; the initial boiling point of the white oil in the upper surface layer and the lower surface layer is not less than 220°C, and the viscosity at 40°C is 40-80mm 2 Optionally or preferably, the initial boiling point of the white oil in the upper surface layer and the lower surface layer is 220-280°C.
[0032] In some specific embodiments, the thickness of the separator is 12-40 μm, and the thickness of the intermediate layer accounts for 40%-80% of the total thickness of the separator.
[0033] A method for preparing the diaphragm comprises the following steps: mixing the raw materials of the upper surface layer, the middle layer and the lower surface layer respectively, co-extruding the three layers, casting the sheets and stretching them, and then drying them to volatilize the white oil.
[0034] In some specific embodiments, during the three-layer co-extrusion process, the extrusion temperature is 160~200°C, and the die temperature is 180~220°C; the temperature of the cast sheet is 50~80°C; the drying temperature is 110~140°C, and the time is 1~5min; the stretching process includes: longitudinal stretching at 80~120°C and transverse stretching at 100~130°C.
[0035] The separator is used in a battery, and the battery is a solid-state battery or a semi-solid-state battery.
[0036] The present invention is described below by specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be thought of by those skilled in the art are included in the present invention, and the attached claims and any equivalents thereof are the protection scope of the present invention.
[0037] Example 1 This embodiment prepares a semi-solid or solid battery separator according to the following steps: S1: Surface preparation Weigh the following surface materials according to weight: 30 parts of high-density polyethylene (M w =6×10 5 Da, polydispersity index is 2, melt index at 190°C is 1g / 10min, melting point is 135°C), 70 parts white oil (initial boiling point is 260°C, viscosity at 40°C is 60mm 2 / s). All the surface layer raw materials are mixed in the mixing silo and then put into the first twin-screw extruder.
[0038] S2: Middle layer preparation Weigh the following intermediate layer materials according to weight: 25 parts of high-density polyethylene (M w =2.5×10 5 Da, polydispersity index of 16, melt index at 190°C of 8 g / 10 min, melting point of 130°C), 70 parts of white oil (flash point of 60°C, viscosity of 2 mm at 40°C 2 / s), 5 parts of polyethylene oxide. All the intermediate layer raw materials are mixed in a mixing silo and then put into the second twin-screw extruder.
[0039] S3: Diaphragm molding The temperature of the first and second twin-screw extruders was set to 180°C. The raw materials were melt-blended and filtered. The material extruded by the first twin-screw extruder was used as the upper surface layer and the lower surface layer, and the material extruded by the second twin-screw extruder was used as the middle layer. The materials were extruded after compounding in a three-layer co-extrusion die. The die temperature was set to 200°C.
[0040] The melt extruded from the three-layer co-extrusion die was cooled at 70°C and a three-layer composite thick sheet was obtained at a pulling speed of 30 m / min. The thick sheet was then longitudinally stretched at 100°C with a stretching ratio of 9.0, and then transversely stretched at 120°C with a stretching ratio of 9.0 to obtain a stretched sheet.
[0041] S4: Drying pores The stretched sheet was dried at 130°C for 5 minutes, pulled, and thickness measured, and then rolled up to obtain the semi-solid or solid battery separator of this embodiment. The separator of this embodiment has a thickness of 20 μm, wherein the thickness of the upper and lower surface layers is 4 μm, and the thickness of the middle layer is 12 μm.
[0042] Example 2 This embodiment prepares a semi-solid or solid battery separator according to the following steps: S1: Surface preparation Weigh the following surface materials according to weight: 50 parts of high-density polyethylene (M w =6×10 5 Da, polydispersity index is 2, melt index at 190°C is 1g / 10min, melting point is 135°C), 50 parts white oil (initial boiling point is 260°C, viscosity at 40°C is 60mm 2 / s). All the surface layer raw materials are mixed in the mixing silo and then put into the first twin-screw extruder.
[0043] S2: Middle layer preparation Weigh the following intermediate layer materials according to weight: 25 parts of high-density polyethylene (M w =2.5×105 Da, polydispersity index of 16, melt index at 190°C of 8 g / 10 min, melting point of 130°C), 70 parts of white oil (flash point of 60°C, viscosity of 2 mm at 40°C 2 / s), 5 parts of polyethylene oxide. All the intermediate layer raw materials are mixed in a mixing silo and then put into the second twin-screw extruder.
[0044] S3: Diaphragm molding The temperature of the first and second twin-screw extruders was set to 180°C. The raw materials were melt-blended and filtered. The material extruded by the first twin-screw extruder was used as the upper surface layer and the lower surface layer, and the material extruded by the second twin-screw extruder was used as the middle layer. The materials were extruded after compounding in a three-layer co-extrusion die. The die temperature was set to 200°C.
[0045] The melt extruded from the three-layer co-extrusion die was cooled at 80°C and a three-layer composite thick sheet was obtained at a pulling speed of 30 m / min. The thick sheet was then longitudinally stretched at 100°C with a stretching ratio of 9.0, and then transversely stretched at 120°C with a stretching ratio of 9.0 to obtain a stretched sheet.
[0046] S4: Drying pores The stretched sheet was dried at 140°C for 4 minutes, pulled, and thickness measured, and then rolled up to obtain the semi-solid or solid battery separator of this embodiment. The separator of this embodiment has a thickness of 20 μm, wherein the thickness of the upper and lower surface layers is 4 μm, and the thickness of the middle layer is 12 μm.
[0047] Example 3 This embodiment prepares a semi-solid or solid battery separator according to the following steps: S1: Surface preparation Weigh the following surface materials according to weight: 30 parts of high-density polyethylene (M w =6×10 5 Da, polydispersity index is 2, melt index at 190°C is 1g / 10min, melting point is 135°C), 70 parts white oil (initial boiling point is 260°C, viscosity at 40°C is 60mm 2 / s). All the surface layer raw materials are mixed in the mixing silo and then put into the first twin-screw extruder.
[0048] S2: Middle layer preparation Weigh the following intermediate layer materials according to weight: 40 parts of high-density polyethylene (M w =2.5×10 5Da, polydispersity index of 16, melt index at 190°C of 8 g / 10 min, melting point of 130°C), 55 parts of white oil (flash point of 60°C, viscosity of 2 mm at 40°C 2 / s), 5 parts of polyacrylonitrile. All the intermediate layer raw materials are mixed in the mixing silo and then put into the second twin-screw extruder.
[0049] S3: Diaphragm molding The temperature of the first and second twin-screw extruders is set to 200°C. The raw materials are melt-blended and filtered. The material extruded by the first twin-screw extruder is used as the upper surface layer and the lower surface layer, and the material extruded by the second twin-screw extruder is used as the middle layer. After compounding in a three-layer co-extrusion die, the extruder is extruded. The die temperature is set to 210°C.
[0050] The melt extruded through the three-layer co-extrusion die was cooled at 70°C and a three-layer composite thick sheet was obtained at a pulling speed of 30 m / min. The thick sheet was then longitudinally stretched at 110°C with a stretching ratio of 9.0, and then transversely stretched at 125°C with a stretching ratio of 9.0 to obtain a stretched sheet.
[0051] S4: Drying pores The stretched sheet was dried at 140°C for 3 minutes, pulled, and thickness measured, and then rolled up to obtain the semi-solid or solid battery separator of this embodiment. The separator of this embodiment has a thickness of 20 μm, wherein the thickness of the upper and lower surface layers is 4 μm, and the thickness of the middle layer is 12 μm.
[0052] Example 4 This embodiment prepares a semi-solid or solid battery separator according to the following steps: S1: Surface preparation Weigh the following surface materials according to weight: 30 parts of high-density polyethylene (M w =6×10 5 Da, polydispersity index is 2, melt index at 190°C is 1g / 10min, melting point is 135°C), 70 parts white oil (initial boiling point is 260°C, viscosity at 40°C is 60mm 2 / s). All the surface layer raw materials are mixed in the mixing silo and then put into the first twin-screw extruder.
[0053] S2: Middle layer preparation Weigh the following intermediate layer materials according to weight: 40 parts of high-density polyethylene (M w =2.5×10 5 Da, polydispersity index of 16, melt index at 190°C of 8 g / 10 min, melting point of 130°C), 50 parts of white oil (flash point of 60°C, viscosity of 2 mm at 40°C2 / s), 10 parts of polyethylene oxide. All the intermediate layer raw materials are mixed in a mixing silo and then put into the second twin-screw extruder.
[0054] S3: Diaphragm molding The temperature of the first and second twin-screw extruders is set to 200°C. The raw materials are melt-blended and filtered. The material extruded by the first twin-screw extruder is used as the upper surface layer and the lower surface layer, and the material extruded by the second twin-screw extruder is used as the middle layer. After compounding in a three-layer co-extrusion die, the extruder is extruded. The die temperature is set to 210°C.
[0055] The melt extruded through the three-layer co-extrusion die was cooled at 70°C and a three-layer composite thick sheet was obtained at a pulling speed of 30 m / min. The thick sheet was then longitudinally stretched at 110°C with a stretching ratio of 9.0, and then transversely stretched at 130°C with a stretching ratio of 9.0 to obtain a stretched sheet.
[0056] S4: Drying pores The stretched sheet was dried at 120°C for 5 minutes, pulled, and thickness measured, and then rolled up to obtain the semi-solid or solid battery separator of this embodiment. The separator of this embodiment has a thickness of 20 μm, wherein the thickness of the upper and lower surface layers is 4 μm, and the thickness of the middle layer is 12 μm.
[0057] Example 5 This embodiment prepares a semi-solid or solid battery separator according to the following steps: S1: Surface preparation Weigh the following surface materials according to weight: 30 parts of high-density polyethylene (M w =6×10 5 Da, polydispersity index is 2, melt index at 190°C is 1g / 10min, melting point is 135°C), 70 parts white oil (initial boiling point is 260°C, viscosity at 40°C is 60mm 2 / s). All the surface layer raw materials are mixed in the mixing silo and then put into the first twin-screw extruder.
[0058] S2: Middle layer preparation Weigh the following intermediate layer materials according to weight: 30 parts of high-density polyethylene (M w =2.5×10 5 Da, polydispersity index of 16, melt index at 190°C of 8 g / 10 min, melting point of 130°C), 70 parts of white oil (flash point of 60°C, viscosity of 2 mm at 40°C 2 / s). All the middle layer raw materials are mixed in the mixing silo and then put into the second twin-screw extruder.
[0059] S3: Diaphragm molding The temperature of the first and second twin-screw extruders was set to 180°C. The raw materials were melt-blended and filtered. The material extruded by the first twin-screw extruder was used as the upper surface layer and the lower surface layer, and the material extruded by the second twin-screw extruder was used as the middle layer. The materials were extruded after compounding in a three-layer co-extrusion die. The die temperature was set to 200°C.
[0060] The melt extruded from the three-layer co-extrusion die was cooled at 70°C and a three-layer composite thick sheet was obtained at a pulling speed of 30 m / min. The thick sheet was then longitudinally stretched at 100°C with a stretching ratio of 9.0, and then transversely stretched at 120°C with a stretching ratio of 9.0 to obtain a stretched sheet.
[0061] S4: Drying pores The stretched sheet was dried at 130°C for 5 minutes, pulled, and thickness measured, and then rolled up to obtain the semi-solid or solid battery separator of this embodiment. The separator of this embodiment has a thickness of 20 μm, wherein the thickness of the upper and lower surface layers is 4 μm, and the thickness of the middle layer is 12 μm.
[0062] Comparative Example 1 The difference between this comparative example and Example 1 is that the diaphragm in this comparative example only uses the surface layer formula. Specifically, the diaphragm in this comparative example is prepared according to the following steps: S1: Prepare materials Weigh the following materials according to weight: 30 parts of high-density polyethylene (M w =6×10 5 Da, polydispersity index is 2, melt index at 190°C is 1g / 10min, melting point is 135°C), 70 parts white oil (initial boiling point is 260°C, viscosity at 40°C is 60mm 2 / s). All raw materials are mixed in the mixing silo and then put into the twin-screw extruder.
[0063] S2: Diaphragm molding The temperature of the twin-screw extruder was set at 180°C. The raw materials were melt-blended, filtered, and extruded through a die. The temperature of the die was set at 200°C.
[0064] The melt extruded from the die was cooled at 70°C and a thick sheet was obtained at a pulling speed of 30 m / min. The thick sheet was then longitudinally stretched at 100°C with a stretching ratio of 9.0, and then transversely stretched at 120°C with a stretching ratio of 9.0 to obtain a stretched sheet.
[0065] S3: Drying pores The stretched sheet was dried at 140° C. for 5 minutes, pulled, and thickness measured, and then rolled up to obtain the semi-solid or solid battery separator of this comparative example. The separator of this comparative example has a thickness of 20 μm.
[0066] Comparative Example 2 The difference between this comparative example and Example 1 is that the separator of this comparative example only adopts the intermediate layer formula. Specifically, the separator of this comparative example is prepared according to the following steps: S1: Prepare materials Weigh the following materials according to weight: 25 parts of high-density polyethylene (M w =2.5×10 5 Da, polydispersity index of 16, melt index at 190°C of 8 g / 10 min, melting point of 130°C), 70 parts of white oil (flash point of 60°C, viscosity of 2 mm at 40°C 2 / s), 5 parts of polyethylene oxide. All raw materials were mixed in a mixing silo and then put into a twin-screw extruder.
[0067] S2: Diaphragm molding The temperature of the twin-screw extruder was set at 180°C. The raw materials were melt-blended, filtered, and extruded through a die. The temperature of the die was set at 200°C.
[0068] The melt extruded from the die was cooled at 70°C and a thick sheet was obtained at a pulling speed of 30 m / min. The thick sheet was then longitudinally stretched at 100°C with a stretching ratio of 9.0, and then transversely stretched at 120°C with a stretching ratio of 9.0 to obtain a stretched sheet.
[0069] S3: Drying pores The stretched sheet was dried at 130° C. for 4 minutes, pulled, and thickness measured, and then rolled up to obtain the semi-solid or solid battery separator of this comparative example. The separator of this comparative example has a thickness of 20 μm.
[0070] Comparative Example 3 The difference between this comparative example and Example 4 is that the white oil in the surface layer of Example 4 is used in both the surface layer and the middle layer of this comparative example, and the white oil is removed by extraction to achieve pore formation. Specifically, this comparative example prepares the diaphragm according to the following steps: S1: Surface preparation Weigh the following surface materials according to weight: 30 parts of high-density polyethylene (M w =6×10 5 Da, polydispersity index is 2, melt index at 190°C is 1g / 10min, melting point is 135°C), 70 parts white oil (initial boiling point is 260°C, viscosity at 40°C is 60mm 2 / s). All the surface layer raw materials are mixed in the mixing silo and then put into the first twin-screw extruder.
[0071] S2: Middle layer preparation Weigh the following intermediate layer materials according to weight: 40 parts of high-density polyethylene (M w =2.5×10 5 Da, polydispersity index of 16, melt index at 190°C of 8 g / 10 min, melting point of 130°C), 50 parts of white oil (initial boiling point of 260°C, viscosity of 60 mm at 40°C 2 / s), 10 parts of polyethylene oxide. All the intermediate layer raw materials are mixed in a mixing silo and then put into the second twin-screw extruder.
[0072] S3: Diaphragm molding The temperature of the first and second twin-screw extruders is set to 200°C. The raw materials are melt-blended and filtered. The material extruded by the first twin-screw extruder is used as the upper surface layer and the lower surface layer, and the material extruded by the second twin-screw extruder is used as the middle layer. After compounding in a three-layer co-extrusion die, the extruder is extruded. The die temperature is set to 210°C.
[0073] The melt extruded through the three-layer co-extrusion die was cooled at 70°C and a three-layer composite thick sheet was obtained at a pulling speed of 30 m / min. The thick sheet was then longitudinally stretched at 110°C with a stretching ratio of 9.0, and then transversely stretched at 130°C with a stretching ratio of 9.0 to obtain a stretched sheet.
[0074] S4: Extraction Pore Formation Dichloromethane was used as an extractant to extract the white oil in the stretched sheet, and after traction and thickness measurement, the semi-solid or solid battery separator of this comparative example was obtained. The separator of this comparative example had a thickness of 20 μm, wherein the thickness of the upper and lower surface layers was 4 μm, and the thickness of the middle layer was 12 μm.
[0075] Comparative Example 4 The difference between this comparative example and Example 4 is that the white oil in the middle layer of Example 4 is used in both the surface layer and the middle layer of this comparative example. Specifically, this comparative example prepares the diaphragm according to the following steps: S1: Surface preparation Weigh the following surface materials according to weight: 30 parts of high-density polyethylene (M w =6×10 5 Da, polydispersity index is 2, melt index at 190°C is 1g / 10min, melting point is 135°C), 70 parts white oil (flash point is 60°C, viscosity at 40°C is 2mm 2 / s). All the surface layer raw materials are mixed in the mixing silo and then put into the first twin-screw extruder.
[0076] S2: Middle layer preparation Weigh the following intermediate layer materials according to weight: 40 parts of high-density polyethylene (M w =2.5×10 5 Da, polydispersity index of 16, melt index at 190°C of 8 g / 10 min, melting point of 130°C), 50 parts of white oil (flash point of 60°C, viscosity of 2 mm at 40°C 2 / s), 10 parts of ion-conducting polymer. All the intermediate layer raw materials are mixed in a mixing silo and then put into the second twin-screw extruder.
[0077] S3: Diaphragm molding The temperature of the first and second twin-screw extruders is set to 200°C. The raw materials are melt-blended and filtered. The material extruded by the first twin-screw extruder is used as the upper surface layer and the lower surface layer, and the material extruded by the second twin-screw extruder is used as the middle layer. After compounding in a three-layer co-extrusion die, the extruder is extruded. The die temperature is set to 210°C.
[0078] The melt extruded through the three-layer co-extrusion die was cooled at 70°C and a three-layer composite thick sheet was obtained at a pulling speed of 30 m / min. The thick sheet was then longitudinally stretched at 110°C with a stretching ratio of 9.0, and then transversely stretched at 130°C with a stretching ratio of 9.0 to obtain a stretched sheet.
[0079] S4: Drying pores The stretched sheet was dried at 120°C for 5 minutes, pulled, and thickness measured, and then rolled up to obtain the semi-solid or solid battery separator of this comparative example. The separator of this comparative example has a thickness of 20 μm, wherein the thickness of the upper and lower surface layers is 4 μm, and the thickness of the middle layer is 12 μm.
[0080] Comparative Example 5 The difference between this comparative example and Example 4 is that the high-density polyethylene in the surface layer of Example 4 is used in both the surface layer and the middle layer of this comparative example. Specifically, this comparative example prepares the diaphragm according to the following steps: S1: Surface preparation Weigh the following surface materials according to weight: 30 parts of high-density polyethylene (M w =6×10 5 Da, polydispersity index is 2, melt index at 190°C is 1g / 10min, melting point is 135°C), 70 parts white oil (initial boiling point is 260°C, viscosity at 40°C is 60mm 2 / s). All the surface layer raw materials are mixed in the mixing silo and then put into the first twin-screw extruder.
[0081] S2: Middle layer preparation Weigh the following intermediate layer materials according to weight: 40 parts of high-density polyethylene (M w =6×10 5 Da, polydispersity index is 2, melt index at 190°C is 1g / 10min, melting point is 135°C), 50 parts white oil (flash point is 60°C, viscosity at 40°C is 2mm 2 / s), 10 parts of ion-conducting polymer. All the intermediate layer raw materials are mixed in a mixing silo and then put into the second twin-screw extruder.
[0082] S3: Diaphragm molding The temperature of the first and second twin-screw extruders is set to 200°C. The raw materials are melt-blended and filtered. The material extruded by the first twin-screw extruder is used as the upper surface layer and the lower surface layer, and the material extruded by the second twin-screw extruder is used as the middle layer. After compounding in a three-layer co-extrusion die, the extruder is extruded. The die temperature is set to 210°C.
[0083] The melt extruded through the three-layer co-extrusion die was cooled at 70°C and a three-layer composite thick sheet was obtained at a pulling speed of 30 m / min. The thick sheet was then longitudinally stretched at 110°C with a stretching ratio of 9.0, and then transversely stretched at 130°C with a stretching ratio of 9.0 to obtain a stretched sheet.
[0084] S4: Drying pores The stretched sheet was dried at 120°C for 5 minutes, pulled, and thickness measured, and then rolled up to obtain the semi-solid or solid battery separator of this comparative example. The separator of this comparative example has a thickness of 17 μm, wherein the thickness of the upper and lower surface layers is 4 μm, and the thickness of the middle layer is 9 μm.
[0085] Test Case The diaphragms prepared according to the methods in the embodiments and comparative examples were cut into A4 size and subjected to performance tests. The test items and methods were as follows: (1) Porosity: The average density of the sample was tested using an electronic balance, and the porosity of the sample was calculated based on the theoretical density. Three samples were tested and their average value was calculated.
[0086] (2) Aperture: The pore size of the samples was tested using a pore size analyzer. Three samples were tested and their average value was calculated.
[0087] (3) Closed-cell temperature: The closed-cell temperature of the sample was tested using a hot stage microscope, and the temperature at which the diaphragm began to melt was recorded. Five samples were tested and the average value was calculated.
[0088] (4) Membrane breaking temperature: The film breaking temperature of the sample was tested using a hot stage microscope, and the temperature of the diaphragm when it began to melt was recorded. Five samples were tested and the average value was calculated.
[0089] (5) Air permeability: The air permeability of the five-layer co-extruded microporous membrane was tested using an air permeability tester. Five samples were tested and the average value was calculated.
[0090] (6) Liquid absorption rate: The liquid absorption rate of the coated diaphragm is tested by weighing method. First, the mass of the diaphragm is recorded after it is completely dried. Then, the completely dried diaphragm is immersed in electrolyte for 24 hours. After the surface electrolyte is wiped dry, the weight of the diaphragm is recorded again. The difference between the two records is the liquid absorption rate of the diaphragm. Test 5 samples and calculate the average value.
[0091] The performance test results of the diaphragm are shown in Table 1.
[0092] Table 1 Performance test results of diaphragm
[0093] From the test results of the embodiments and comparative examples shown in Table 1, it can be seen that: (1) Compared with Comparative Examples 1 and 2, Example 1 has higher porosity, pore size and liquid absorption rate. This shows that the present invention designs the diaphragm into a three-layer structure and uses differentiated high-density polyethylene and white oil in the surface layer and the middle layer, which can make the diaphragm have a larger pore size and porosity. This property enables the diaphragm to accommodate more electrolyte when used in solid-state or semi-solid-state batteries.
[0094] (2) Compared with Comparative Example 3, Example 4 has higher porosity, pore size and liquid absorption rate. This is because: the white oil used in the surface layer and the middle layer of Comparative Example 3 is difficult to volatilize and needs to be removed by extraction; Example 4 uses white oil that is easy to volatilize in the middle layer, and uses the volatilization of the white oil in the middle layer to drive the surface white oil to leave the diaphragm. Compared with the static extraction method, the dynamic volatilization method can obtain a larger porosity and pore size.
[0095] (3) Compared with Comparative Example 4, Example 4 has higher porosity, pore size and liquid absorption rate. This is because: Comparative Example 4 uses easily volatile white oil in both the surface layer and the middle layer, and more white oil will evaporate prematurely during the membrane forming process, resulting in less white oil that can play a pore-forming role during the drying process after forming, and the volatilization rate of the white oil during the drying process is too fast; in Example 4, white oil with a higher initial distillation point is used in the surface layer, which is not easy to evaporate during the membrane preparation and forming process, so it can slow down the volatilization of the white oil in the middle layer and reduce the premature volatilization loss of the white oil in the middle layer. In addition, during the drying process after the membrane is formed, the white oil in the surface layer is driven to leave the membrane together with the white oil in the middle layer during the volatilization process. Due to the lower volatilization rate of the surface white oil, the volatilization process of the middle layer white oil can be made more controllable.
[0096] (4) Compared with Comparative Example 5, Example 4 has higher porosity, pore size and liquid absorption rate. This is because: Comparative Example 5 uses high-density polyethylene with a large molecular weight and a narrow distribution range in both the surface layer and the middle layer, and the middle layer is not easy to expand in thickness with the volatilization of the white oil therein; Example 4 uses high-density polyethylene with a small molecular weight and a wide distribution range in the middle layer. During the drying process, as the white oil evaporates, the middle layer is easy to expand in thickness, further increasing the porosity and pore size of the diaphragm.
[0097] Unless otherwise defined, all technical terms and scientific terms used in the present invention have the same meanings as those commonly understood by ordinary technicians in the field to which the present disclosure belongs. Unless otherwise specified, the raw materials and equipment used in the present invention are conventional raw materials and equipment in the field and can be obtained from conventional commercial channels; unless otherwise specified, the methods used in the present invention are conventional methods in the field.
[0098] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A semi-solid or solid battery separator, characterized in that: It includes an upper surface layer, an intermediate layer and a lower surface layer arranged in sequence from top to bottom; the raw materials of the intermediate layer include: a weight average molecular weight of 2×10 5 ~3×10 5 Da and a polydispersity coefficient of 12 to 20, and a white oil with a flash point not higher than 80°C; the raw materials of the upper surface layer and the lower surface layer include: a weight average molecular weight of 6×10 5 ~1×10 6 Da high-density polyethylene, white oil with an initial distillation point higher than the diaphragm molding temperature.
2. The diaphragm according to claim 1, characterized in that The raw materials of the intermediate layer include, by weight: 5 ~3×10 5 20 to 45 parts of high-density polyethylene with a Da and a polydispersity index of 12 to 20, 50 to 70 parts of white oil with a flash point not higher than 80°C, and 1 to 10 parts of an ion-conducting polymer.
3. The diaphragm according to claim 1, characterized in that The raw materials of the upper surface layer and the lower surface layer are calculated by weight: 5 ~1×10 6 30-50 parts of high-density polyethylene of Da, 50-70 parts of white oil with an initial boiling point higher than the diaphragm molding temperature.
4. The diaphragm according to claim 1 or 2, characterized in that: The high-density polyethylene in the middle layer has a melt index of 7-10 g / 10 min at 190°C and a melting point of no higher than 135°C; the viscosity of the white oil in the middle layer is 1-5 mm at 40°C. 2 / s.
5. The diaphragm according to claim 1 or 3, characterized in that: The polydispersity coefficient of the high-density polyethylene in the upper surface layer and the lower surface layer is less than 3, the melt index at 190°C is 0.1~2g / 10min, and the melting point is not less than 130°C; the initial boiling point of the white oil in the upper surface layer and the lower surface layer is not less than 220°C, and the viscosity at 40°C is 40~80mm 2 / s.
6. The diaphragm according to claim 2, characterized in that The ion-conducting polymer includes one or more of polyethylene oxide, polyacrylonitrile, polyvinyl alcohol and polymethyl methacrylate.
7. The diaphragm according to claim 1, characterized in that The thickness of the diaphragm is 12-40 μm, and the thickness of the middle layer accounts for 40%-80% of the total thickness of the diaphragm.
8. A method for preparing a diaphragm according to any one of claims 1 to 7, characterized in that the steps include: The raw materials of the upper surface layer, the middle layer and the lower surface layer are mixed separately, and then three layers are co-extruded, cast into sheets and stretched, and then dried to volatilize the white oil.
9. The preparation method according to claim 8, characterized in that: During the three-layer co-extrusion process, the extrusion temperature is 160-200°C, the die temperature is 180-220°C; the temperature of the cast sheet is 50-80°C; the drying temperature is 110-140°C, and the time is 1-5 minutes; the stretching process includes: longitudinal stretching at 80-120°C and transverse stretching at 100-130°C.
10. Use of the separator according to any one of claims 1 to 7 in a battery, characterized in that: The battery is a solid-state battery or a semi-solid-state battery.
Citation Information
Patent Citations
Battery isolating membrane
CN108242523A
Composite diaphragm, electrochemical device, electronic equipment and mobile terminal
CN115693024A
Heat shrink film with microporous structure and preparation method thereof
CN116215039A
Polyethylene lithium battery diaphragm and production process thereof
CN116387756A
Production method of novel ultrahigh-porosity polyethylene diaphragm
CN117134069A